True thymic hyperplasia causing pure red cell aplasia: a case report. (13th November 2021) - Mohammad, Adam; Dawson, Alan G; Bajaj, Amrita; Rathinam, Sridhar
Abstract: Pure red cell aplasia caused by true thymic hyperplasia is extremely rare. We report the case of a 25-year-old female diagnosed with pure red cell aplasia. Following a thymectomy confirming true thymic hyperplasia and corticosteroid therapy, complete response was achieved. Patients diagnosed with pure red cell aplasia should be investigated with a computerized tomographic scan to assess for thymic pathology and if present, this should be resected. Follow-up is essential to monitor for recurrence. Abstract : Pure red cell aplasia (PRCA) is typified by a severe normochromic, normocytic anaemia associated with a reticulocytopaenia and an absence of erythroblasts from the bone marrow with preserved granulopoiesis and megakaryopoiesis [1].